PERAN MASYARAKAT PESISIR TERHADAP PENGELOLAAN TERUMBU KARANG DI KAWASAN KONSERVASI PERAIRAN PESISIR TIMUR PULAU WEH - Nurul Najmi; Mai Suriani; Mira Mauliza Rahmi; Dini Islama; Muhammad Arif Nasution (JURNAL PERIKANAN TROPIS, 2020)
The role of coastal communities in the preservation of coral reefs is an important thing to supporting the sustainable management of coastal areas. This article is objected to determine the coastal communities’ role in the management of coral reefs in water conservation areas and the level of knowledge of the coastal communities about the importance of protecting coastal ecosystems. Data were collected by distributing questionnaires, direct interviews and Focus Group Discussions (FGD) and the results were elaborated based on descriptive analysis. The results showed that the community had begun to realize how important it is to protect coral reefs for the sustainability of fisheries and other benefits of coral reefs. Healthy reefs provide many benefits to people including improving the economy of the community and increasing tourists. Community awareness is shown by their participation in activities that lead to the conservation and management of coral reefs such as transplantation of coral reefs, beach cleaning, banner making, tree planting and provision of trash bins along the coast. Those who knew the benefits and functions of coral reefs both for increasing fish populations, increasing tourists and improving the economy of the community, as well as other benefits of coral reefs for the coastal areas, was 74.5%. The role of community in the aspects of coastal and marine ecosystems management was high, as many as 72% of the community participate in every coastal and marine ecosystem management activity carried out by the government and local NGOs.